Anticaries Effect of Ethanol Extract of Terminalia chebula - Moonkyung Lee; Young Sun Hwang (The Korean Society of Dental Hygiene Science, 2021)
Background: Dental caries is mainly composed of various cellular components and is deposited around the tooth surface and gums, causing a number of periodontal diseases. Streptococcus mutans is commonly found in the human oral cavity and is a significant contributor to tooth decay. The use of antibacterial ingredients in oral hygiene products has demonstrated usefulness in the management of dental caries. This study investigated the anticaries effect of the ethanol extract of Terminalia chebula (EETC) against S. mutans and their cytotoxicity to gingival epithelial cells. Methods: The EETC was prepared from T. chebula fruit using ethanol extraction. Disk diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and colony forming unit (CFU) were analyzed to investigate the antimicrobial activity of the EETC. Glucan formation was measured using the filtrate of the bacterial culture medium and sucrose. Gene expression was analyzed using reverse transcription-polymerase chain reaction (RT-PCR). Cytotoxicity was analyzed via the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay. Results: The antibacterial activity of the EETC was explored using disc diffusion and CFU measurements. The MIC and MBC of the EETC were 10 and 20 μg/ml, respectively. EETC treatment decreased insoluble glucan formation by S. mutans enzymes and also resulted in reduced glycosyltransferase B (gtf B), gtf C, gtf D, and fructosyltransferase (ftf), expressions on RT-PCR. In addition, at effective antibacterial concentrations, EETC treatment was not cytotoxic to gingival epithelial cells. Conclusion: These results demonstrate that the EETC is an effective anticaries ingredient with low cytotoxicity to gingival epithelial cells. The EETC may be useful in antibacterial oral hygiene products for the management of dental caries.